2014
DOI: 10.1002/cctc.201300987
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platinum Nanoparticle Distribution on Oxygen Electroreduction Activity and Selectivity

Abstract: The catalytic activity and selectivity of Pt nanoparticles towards the oxygen reduction reaction (ORR) were investigated as a function of the Pt catalyst distribution. By means of the sputtering deposition technique, it was possible to fabricate Pt catalysts with different loadings that consisted of dispersed 2–3 nm particles, nanoparticle agglomerates and extended particulate layers. The transition from dispersed nanoparticles to extended layers led to a decrease in the electrochemical surface area (ECSA, m2P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 43 publications
19
70
0
Order By: Relevance
“…1, and hence an overall reduction in the active Pt surface area. This effect was also observed by our groups in a study on sputtered model electrodes with increasing Pt loadings [21]. López-Cudero et al also reported on a system with increasing Pt loading on carbon (from 10 to 50 wt%) but did not observe the trend of decreasing ECSA with higher loading [27].…”
Section: Electrochemically Active Surfacesupporting
confidence: 82%
See 2 more Smart Citations
“…1, and hence an overall reduction in the active Pt surface area. This effect was also observed by our groups in a study on sputtered model electrodes with increasing Pt loadings [21]. López-Cudero et al also reported on a system with increasing Pt loading on carbon (from 10 to 50 wt%) but did not observe the trend of decreasing ECSA with higher loading [27].…”
Section: Electrochemically Active Surfacesupporting
confidence: 82%
“…Hydrogen peroxide formation was seen to be greatest on the low loading, isolated platinum nanoparticle surface. Findings from this study support the presence of a serial reaction pathway for the ORR via a H 2 O 2 intermediate on a peroxide desorption-readsorption pathway [21]. Extending this study to a practical catalyst system, we here present a study based on the preparation of platinum supported on carbon catalysts by thermally induced chemical deposition with increasing platinum loadings on the support.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Typically, active catalysts for the HER also show good oxygen reduction reaction (ORR) performances, as has been intensively studied, such as Pt [40][41][42][43] and multi-metal catalysts. [44][45][46][47][48][49] Therefore, the evolved oxygen, which can be transported from the anode to the cathode, is reduced back to a water molecule.…”
mentioning
confidence: 99%
“…7 Several techniques have been explored in an attempt to produce efficient Pt electrocatalysts including chemical and physical methods such as chemical reduction [8][9][10] or sputter deposition techniques. [11][12][13] However, these techniques either lead to high metal loading with poor control of the size distribution or have proven difficult to scale up. 9,14 Although great effort has been made toward the development of chimie douce production of shape-controlled Pt nanoparticles, hierarchical nanostructures with high specific surface area remain a challenge.…”
mentioning
confidence: 99%